Emotional words evoke region- and valence-specific patterns of concurrent neuromodulator release in human thalamus and cortex - Seth R. Batten; Alec E. Hartle; Leonardo S. Barbosa; Beniamino Hadj-Amar; Dan Bang; Natalie Melville; Tom Twomey; Jason P. White; Alexis Torres; Xavier Celaya; Samuel M. McClure; Gene A. Brewer; et al. (Cell Reports)
Summary: Words represent a uniquely human information channel—humans use words to express thoughts and feelings and to assign emotional valence to experience. Work from model organisms suggests that valence assignments are carried out in part by the neuromodulators dopamine, serotonin, and norepinephrine. Here, we ask whether valence signaling by these neuromodulators extends to word semantics in humans by measuring sub-second neuromodulator dynamics in the thalamus (N = 13) and anterior cingulate cortex (N = 6) of individuals evaluating positive, negative, and neutrally valenced words. Our combined results suggest that valenced words modulate neuromodulator release in both the thalamus and cortex, but with region- and valence-specific response patterns, as well as hemispheric dependence for dopamine release in the anterior cingulate. Overall, these experiments provide evidence that neuromodulator-dependent valence signaling extends to word semantics in humans, but not in a simple one-valence-per-transmitter fashion.